Research on the Fusion Model of Professional Vocal Music Performance Voice Care and Artificial Intelligence Technology in Intelligent Medical Treatment. (9th May 2022) - Qin, Wei; Lin, Qingna
Abstract : Intelligent medical treatment is an important research field in today's world. Artificial intelligence technology is the key factor to construct intelligent medical treatment. In the development of artificial intelligence technology, it is necessary to establish a scientific, systematic, and comprehensive system analysis model, inevitably with certain professional characteristics. At present, in the research of vocal health care in professional vocal music performance, the application of intelligent medical care and vocal health care in professional vocal music performance is studied. According to the DEMATEL-ISM research method, this paper constructs 4 internal and external factors and 16 influencing factors to build a comprehensive and systematic weight analysis model, which provides a theoretical and practical basis for the scientific construction of AI technology algorithms. The aim is to improve the value and research significance of intelligent medical artificial intelligence technology in professional vocal music performance sound care.